Christianity and constitutionalism - Aroney, Nicholas; Leigh, Ian (Oxford University Press, 2022)
A groundbreaking new collection, Christianity and Constitutionalism offers a variety of interdisciplinary perspectives on the relationship between Christian thought, history, and practice, and constitutional law and its related fields.